Effect of annealing on the optical properties of TiO2 films - Prikhodko, Oleg; Mikhailova, Svetlana; Mukhametkarimov, Yerzhan; Maksimova, Suyumbika; Dauitkhan, Kuanysh; Doseke, Ulantai (The 8th International Conference on Nanomaterials and Advanced Energy Storage Systems; Nazarbayev University; National Laboratory Astana; Institute of Batteries, 2020)
In this work, TiO2 films, which were obtained by ion-plasma high-frequency magnetron sputtering of a polycrystalline rutile target in an argon atmosphere at 1 Pa pressure were studied. The TiO2 films were annealed for 1 hour in air in the temperature range from 100 °C to 400 °C with 100 °C increment. It was found that the TiO2 films have high transparency, which remains almost unchanged during annealing. The fundamental absorption edge of the films, which is located from 320 to 380 nm, also changes slightly with increasing annealing temperature up to 400 °C. The refractive index n(λ) of the films decreases with incident radiation increasing and, as a result, TiO2 films are characterized by normal dispersion. With increasing annealing temperature, the refractive index n in the long-wavelength region of the spectrum increase in comparison with those in films without annealing. When comparing the calculated values of n(λ) with theoretical values, one can see that in the short-wavelength region of the spectrum, the dependences n(λ) coincide, while discrepancies are observed with wavelength increasing. This may be due to the structural features of the films, which depend on their thickness. In a literature, the refractive index of titanium dioxide was measured for samples with ~ 1-2 μm thickness, while in this work the films with ~ 270 nm thickness were studied. From the calculated n(λ), we can conclude that for TiO2 films the optical properties are stable up to a temperature of 600 °C. It was found that the absorption laws are equally well satisfied for the studied TiO2 films before and after annealing. This means that for TiO2 films before and after annealing at 400 °C, the realization of direct and indirect optical transitions upon absorption of light quanta is equally probable. Optical band gap of the films annealed at 400 °C, determined from the quadratic absorption law, was ~ 3.01 eV, which is typical for TiO2 films with a rutile structure. This Eg is significantly less than the value obtained using the law with γ = 1/2, which corresponds to the allowed direct-gap optical transitions.
Keywords: optical properties of TiO2 films; TiO2 films; effect of annealing; Research Subject Categories::TECHNOLOGY